The protective role of propolis against road transport stress in sheep before slaughter - Seven, Ismail; Kilic, Sabriye; Mutlu, Seda Iflazoglu; Mutlu, Muhsin; Aslan, Abdullah; Cicek, Miray Sila; Seven, Pinar Tatli (Springer, 2025)
This study was conducted to minimize and prevent yield losses due to stress situations during animal transport. Thirty-six 12-month-old male yearling Akkaraman sheep were divided into three groups: Control, P75 (75 mg/kg body weight), and P150 (150 mg/kg body weight); a single oral dose of propolis was administered 12 h before transport. The animals' live weights were weighed before and after transport (381.7 km, approximately 8.5 h). It was determined that the live weight losses in the Control, P75, and P150 groups due to transportation were statistically significant (P < 0.05). It was determined that there were statistically significant differences within the group in the blood glucose, cholesterol, aspartate aminotransferase (AST), alkaline phosphatase (ALP) and creatine kinase (CK) of all groups, malondialdehyde (MDA) of Control and P75 groups, triglyceride of Control and P150 groups, total protein and creatinine of P75 and P150 groups, urea of Control group, gamma-glutamyl transferase (GGT) of P75 group, and very-low-density lipoprotein (VLDL) of P150 group (P<0.05). Additionally, it was determined that there were statistically significant differences between the groups in glucose, triglyceride, AST, CK, creatinine, and MDA values due to transportation stress (P<0.05). The MDA, glutathione, and glutathione peroxidase values of liver tissues taken from yearlings after slaughter were statistically different from the Control group in the P75 and P150. In contrast, the catalase values were statistically different from each other in all groups. The fatty acid composition and pH analysis of muscle tissues showed insignificant group differences. As a result, it was determined that the different doses of propolis used in this study significantly reduced the transportation stress of Akkaraman sheep.
Keywords: Sheep; Transport; Propolis; Stress; Meat quality